Using Cognitive Neuroscience Research Findings in Designing Pedagogical Tools for Adolescent Learners - Manwani, Kamal G. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
To ensure desired learning outcomes, a lot is being done in the areas of developing better curriculum, making state of the art schools, improving teacher quality, incorporating ICT, enhancing parental involvement etc. However, when it comes to designing Pedagogical Tools based on the learning patterns of the brain, there exists a wide gap between what is researched in laboratories and what is experienced in our classrooms. Pedagogical practices not based on an understanding of brain‟s functioning can lead to Cognitive Overload in learners causing undesired behavioural consequences in them, especially in Adolescent Learners. This paper looks into various researches that have been done in Cognitive Neuroscience and their educational implications on Adolescent Learners. This paper suggests that pedagogical practices must create a learning environment that utilizes brain‟s pattern of learning. It explores why Teacher Training must include training Student Teachers in cognitive aspects of an adolescent‟s brain like role of reward system, enhancing Working Memory, providing multisensory stimulus to learners, using memory strategies, understanding learning loops etc. This paper concludes how learnings from these Cognitive Neuroscience researches can address the issue of High Riskbehaviour tendencies amongst adolescent learners